2008
DOI: 10.1186/1742-4690-5-117
|View full text |Cite
|
Sign up to set email alerts
|

Human cellular microRNA hsa-miR-29a interferes with viral nef protein expression and HIV-1 replication

Abstract: Background: Cellular miRNAs play an important role in the regulation of gene expression in eukaryotes. Recently, miRNAs have also been shown to be able to target and inhibit viral gene expression. Computational predictions revealed earlier that the HIV-1 genome includes regions that may be potentially targeted by human miRNAs. Here we report the functionality of predicted miR-29a target site in the HIV-1 nef gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
231
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(243 citation statements)
references
References 34 publications
10
231
0
2
Order By: Relevance
“…Using target prediction software, they identified five miRNA (miR-29a, miR29b, miR-149, miR-324-5p, and miR-378) target sites in the HIV-1 genome, with two of these sites located in the viral nef gene (31). These investigators confirmed later that one of the five identified miRNAs (miR-29a) inhibited nef expression, leading to repressed HIV replication in Jurkat cells (32). This effect was also observed by Rana and colleagues (33), who predicted target sites for 11 miRNAs in the HIV-1 3Ј-UTR and further experimentally validated an inhibitory effect of miR-29a on HIV replication.…”
Section: Cellular Mirnas Regulate Hiv-1 Expressionsupporting
confidence: 68%
“…Using target prediction software, they identified five miRNA (miR-29a, miR29b, miR-149, miR-324-5p, and miR-378) target sites in the HIV-1 genome, with two of these sites located in the viral nef gene (31). These investigators confirmed later that one of the five identified miRNAs (miR-29a) inhibited nef expression, leading to repressed HIV replication in Jurkat cells (32). This effect was also observed by Rana and colleagues (33), who predicted target sites for 11 miRNAs in the HIV-1 3Ј-UTR and further experimentally validated an inhibitory effect of miR-29a on HIV replication.…”
Section: Cellular Mirnas Regulate Hiv-1 Expressionsupporting
confidence: 68%
“…Several cellular miRNAs (miRNA-28, miRNA-29a, miRNA125b, miRNA-150, miRNA-198, miRNA-223, and miRNA-382) target a set of accessory genes of HIV. [23][24][25][26][27] For example, these miRNAs can target the 3=-UTR of HIV transcripts, 28 potentially rendering productive infection of HIV into latency in resting CD4 ϩ T lymphocytes. Recently, it was reported that monocytes express significantly higher levels of anti-HIV miRNAs than donormatched macrophages, thereby unraveling the refractory nature of monocytes to HIV infection.…”
mentioning
confidence: 99%
“…They used target prediction software and identified five miRNA target sites in the HIV genome: miR-29a, miR-29b, miR-149, miR-324-5p, and miR-378. Another study by Ahluwalia et al confirmed that miR-29a inhibited nef expression, leading to repressed HIV replication in Jurkat cells [12]. Further experiments validated an inhibitory effect of miR-29a on HIV replication and also predicted target sites for 11 miRNAs in the HIV-1 3' UTR [14].…”
Section: Mirnas Directly Targeting Hiv Rnamentioning
confidence: 67%
“…Bioinformatics analyses also have extended this notion of antiviral defense to diverse human miRNAs that can target many types of viruses [10]. Specifically, miRNA-regulation of HIV-1 infection has been experimentally verified and independently reported by several groups of investigators [11][12][13][14][15]. Previously, we have discussed the role of micRNAs on tuberculosis infection and also other non-communicable disease [10,16,17].…”
Section: Introductionmentioning
confidence: 99%